La comunicación, como una estrategia adicional para la gestión del cambio organizacional en Asecofin S.A.S (2020)
The present work consists of the design and documentation work of different communication strategies aligned to a change management methodology in the implementation of the quality management system of Asecofin SAS. Upon arriving at Asecofin, it was evident that there was no communication in or between his processes, their collaborators did not perceive themselves motivated, listened to, valued or empowered. As it is a family organization, it was highlighted that all decisions were centralized in the general manager, although they worked in the development of the quality management system many of its collaborators and Contractors did not know about this project, they had tools like Moodle underutilized and their communications were deficient as they lacked strategy and objective. As in any organization, Asecofin's internal and external client must know the benefits of implementing a quality management system with the objective of achieving continuous improvement. To do this, use the NTP methodology 581: "Management of organizational change" (National Institute of Safety and Hygiene at Work, 2001). And I designed, developed and implemented different strategies of communication to disseminate the QMS articulated with change management. I conducted a general survey in the organization prior to the start of the project that evidenced the centralization of decision-making and the blockages that this produced, the lack of communication with all hierarchical levels, the perception of apathy on the part of Asecofin with its collaborators and contractors, the lack of training and empowerment of employees and the need to transform a tax communication by a participatory communication and in double via. After the stage of implementation and validation of the results, I found a much more cohesive panorama in the organization. Thanks to the strategies communication the perception of collaborators, contractors and clients change favorably giving Asecofin the opportunity to be an organization that supports business sustainability on communication.